The Impact of Managerial Performance on Effective Public Governance at Higher Education Institutions in Java, Indonesia - Petrolis Nusa Perdana; Hera Khairunnisa; David Al Khabib Ardinda (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: This research examines the influence of Academic Services (AS), Regulatory Compliance (RC), and Fund Allocation (FA) as part of Management Performance on the Good Public Governance (GPG) of higher education institutions in Java, Indonesia. Design/Methodology/Approach: Drawing upon stakeholder theory, this research employs Partial Least Squares Structural Equation Modelling (PLS-SEM), analysed using SmartPLS 4.0. The research involves 15 higher education institutions, three government agencies, and one regional leader. Research findings: The findings indicate that AS and FA demonstrate a measurable effect on GPG, aligning with stakeholder theory by addressing the dynamic needs of stakeholders, while RC shows no measurable influence. Theoretical contribution/Originality: These results highlight the importance of aligning management practices with stakeholder needs to improve public governance in higher education. Practitioner/Policy implication: The research offers practical insights for university administrators and policymakers to enhance GPG through integrated strategies, ultimately contributing to the improvement of public governance. Research limitation: The study’s limited sampling, subjectivity, and respondent biases.